2008
DOI: 10.1111/j.1365-2702.2006.01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two blood sampling methods in anticoagulation therapy: venipuncture and peripheral venous catheter

Abstract: In clinical applications, nurses may prefer the use of peripheral venous catheter to venipuncture both for the comfort of the patients who get anticoagulation therapy and for the prevention of the risks as a result of venipuncture. Application of peripheral venous catheter eliminates the risks of superficial bleeding, irritation, pain and anxiety caused by venipuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…This is in agreement with the human literature, where sampling from an IVC compared to direct venipuncture had no effect on the analysis of coagulation profiles [14,15]. With the exception of AT and D-dimers, agreement between sample types was good and the sensitivity and specificity of catheter samples compared to direct venipuncture samples were high overall.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the human literature, where sampling from an IVC compared to direct venipuncture had no effect on the analysis of coagulation profiles [14,15]. With the exception of AT and D-dimers, agreement between sample types was good and the sensitivity and specificity of catheter samples compared to direct venipuncture samples were high overall.…”
Section: Discussionsupporting
confidence: 90%
“…Although our study analysed the prothrombin ratio, others, such as those of Zlotowski et al 20 and Zengin et al ,25 used prothrombin time, finding equivalency and no difference in mean between the methods.…”
Section: Discussionmentioning
confidence: 48%
“…Flush the sampling port with 10 mL of normal saline. 5. Attach an empty 10-mL syringe to the sampling port, and withdraw 6 mL of blood and discard.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a 2008 Turkish study, researchers compared PT and PTT results drawn concurrently from PIVs and VPs and found no clinically significant difference in results when a 1-mL blood discard was used. 5 Finally, in 53 pediatric oncology patients, after testing discard volumes of 6, 9, and 12 mL from a heparinized tunneled venous access device, researchers concluded that coagulation samples (PT, PTT, and fibrinogen) drawn from a heparinized tunneled venous access device after any discard volume did not yield trustworthy results compared with VP. 6 Researchers also addressed the accuracy of serum test results drawn from 2 peripheral sites.…”
Section: Literature Reviewmentioning
confidence: 98%